Childhood cancer survivors’ struggle for social integration after treatment a mixed-methods exploration of activity and participation - Verena Paul; Laura Inhestern; Désirée Sigmund; Jana Winzig; Annette Sander; Stefan Rutkowski; Gabriele Escherich; Corinna Bergelt (PLoS ONE, 2026)
Purpose Childhood cancer presents lasting challenges beyond primary treatment, affecting multiple aspects of daily life. This mixed-methods study examines the impact of childhood cancer on activities and participation within the first five years after treatment. It mainly focuses on the interplay of factors influencing participation. Further, qualitative interviews provide contextual insights and experiential perspectives from affected families to complement the quantitative findings. Methods The study combines qualitative interviews with 30 parents and quantitative survey data from 256 parents. The survey included self-developed items based on the International Classification of Functioning, Disability and Health (ICF). A correlation-based network analysis examined relationships among factors affecting children’s activities and participation. Results Survivors experience impairments in school activities, social interactions, and daily functioning. Network analysis highlights the interconnections among ICF-coded aspects, revealing that learning, communication, and participation in major life areas strongly influence overall activity and participation. Conclusion While many survivors reintegrate into everyday life, hidden challenges can significantly impact their participation. This study underscores the need for a holistic, multidisciplinary approach addressing medical, educational, and psychosocial challenges, including struggles beyond visible limitations. Implications Interventions should prioritize comprehensive support, particularly in learning, communication, and participation in school activity. Educating healthcare providers and caregivers about the interdisciplinary links between these domains is essential for a coordinated, holistic approach.